Wisdom toward Nature: A Perennial Approach to the Cultural Perspective of Indigenous People in Indonesia - Halim, Ilim Abdul; Hambali, R. Yuli A.; Marjani, Gustiana Ishak; Sidik, Mohamad Dindin Hamam (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2025)
This article examines a customary society’s approach to environmental conservation, particularly the indigenous group in Cikondang village, Bandung Regency. This article employs a case study approach to understand their local wisdom toward nature. In addition, this study adopts a perennial philosophy perspective, which considers nature and humanity as integral parts of a divine macro and micro cosmos, necessitating mutual protection and harmony. The study reveals that the Cikondang people adhere to the philosophy of mipit kudu amit, ngala kudu bebeja (picking requires permission, taking must be declared), which underscores not only a prohibition against theft but also an ethical commitment to environmental sustainability. This principle is manifested in the strict protection of sacred areas such as huluwotan (spring sources) and prohibited forests, which are safeguarded against exploitation. The study shows the significance of indigenous beliefs and practices in promoting ecological balance, providing crucial insights for contemporary environmental management.